2016
DOI: 10.1016/j.ijid.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Spirometra mansoni in dogs, cats, and frogs and its medical relevance in Guangzhou, China

Abstract: A high sparganum infection rate was observed in the wild frogs sold in agricultural product markets in Guangzhou. The infection was also serious in cats and dogs in Guangdong Province. With lifestyles and eating habits resulting in sparganum infection, it is necessary to focus on market management and community education in order to prevent the transmission of this disease in Guangzhou.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…The first intermediate hosts for the parasite are copepods, and the second intermediate hosts are amphibians and reptiles, including frogs and snakes (Hong et al . 2016; Kondzior et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first intermediate hosts for the parasite are copepods, and the second intermediate hosts are amphibians and reptiles, including frogs and snakes (Hong et al . 2016; Kondzior et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…infestations (Hong et al . 2016), while wild carnivores contract them sporadically (Scioscia et al . 2014; Almeida et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, A. abstrusus could not be excluded as they with high Spirometra spp. infestation [25], while wild carnivores were ones sporadically [26] [27]. As far as the wild felines were concerned, the Panthera leo [28], Lynx lynx [24], leopardus pardalis [26], Lynx rufus, Oncifelis guigna, Puma concolor, Panthera onca, [27] and Panthera tigris [11] deer, which contains juvenile worms [35] [36] [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the cities of Yunfu and Zhaoqing the prevalence of infection by S. erinaceieuropaei was of 47.2% and 12.6%, respectively in dogs. Infection in the cats was of 64.4% and 35.9% in Yunfu and Zhaoqing, respectively (Hong et al, 2016). Treatment of wild definitive mammal hosts (others canids and felids) is difficult.…”
Section: Hygiene Measuresmentioning
confidence: 99%
“…Eating well-cooked frogs or aquatic snakes prevent the infection (Anantaphruti et al 2011;Liu et al 2015). Hong et al (2016) determined through a survey that the consumption of cooking meat with frying and/or porridge and/or soup would be the most probable means of transmission of sparganosis by frogs in Guangzhou, China. These authors found prevalences of 51.2% and 35.1% in wild R. tigrina rugulosa and R. limnocharis, however, sparganosis was not found in farmed frogs.…”
Section: Hygiene Measuresmentioning
confidence: 99%